Teacher Empowerment and Training in Developing Digital Teaching Materials at SMP Negeri 25 Barru: Pemberdayaan dan Pelatihan Guru dalam Pembuatan Bahan Ajar Digital di SMP Negeri 25 Barru - Rahman, Abdul; Rusli, R.; Iskandar, Akbar; Ahmar, Ansari Saleh (Yayasan Ahmar Cendekia Indonesia, 2024)
This training is in the form of training on creating digital learning materials using Heyzine at SMP Negeri 25 Barru. This training aims to equip teachers with the skills to create interactive and visually appealing learning resources. The training, held on August 22, 2024, used a workshop model consisting of two stages: theory sessions and practical sessions. The results showed significant improvement in teachers' ability to develop engaging and interactive materials, with increased confidence in using digital tools to support learning objectives. In addition, teachers gained insights into the use of technology to create meaningful educational experiences, and some teachers began to integrate Heyzine with other digital platforms such as Google Classroom. Overall, the training reflected a proactive approach to preparing educators for future educational challenges in an increasingly digitized world. Abstrak Pelatihan ini berupa pelatihan pembuatan materi pembelajaran digital menggunakan Heyzine di SMP Negeri 25 Barru. Pelatihan ini bertujuan untuk membekali para guru dengan keterampilan membuat sumber belajar yang interaktif dan menarik secara visual. Pelatihan yang diselenggarakan pada tanggal 22 Agustus 2024 ini menggunakan model lokakarya yang terdiri dari dua tahap: sesi teori dan sesi praktik. Hasilnya menunjukkan peningkatan yang signifikan dalam kemampuan guru untuk mengembangkan materi yang menarik dan interaktif, dengan peningkatan kepercayaan diri dalam menggunakan alat digital untuk mendukung tujuan pembelajaran. Selain itu, para guru memperoleh wawasan tentang penggunaan teknologi untuk menciptakan pengalaman pendidikan yang bermakna, dan beberapa guru mulai mengintegrasikan Heyzine dengan platform digital lainnya seperti Google Classroom. Secara keseluruhan, pelatihan ini mencerminkan pendekatan proaktif untuk mempersiapkan para pendidik dalam menghadapi tantangan pendidikan di masa depan di dunia yang semakin terdigitalisasi.